Comparision of ultrasonographic diagnosis with ‘Tzanakis’ Score in acute appendicitis - Rajbhandari, Ashish Prasad; Dhakal, Nischal; Koirala, Robin; Shrestha, Manohar Lal (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Acute appendicitis is one of the most common acute surgical abdominal conditions requiring surgery. Ever since the inflamed appendix was demonstrated in the 1980’s by Ultrasonography, it has been used as an aid to clinically diagnose acute appendicitis. Tzanakis scoring system is a combination of clinical examination, Ultrasonography and inflammatory markers. Methods: A retrospective non-randomized observational study was conducted from April 2014 to March 2015 on all cases of acute appendicitis, which underwent preoperative ultrasound before appendectomy (open/laparoscopic) at the Department of surgery, Nepal Medical College Teaching Hospital. Ultrasound findings and Tzanaki score were compared in the cases. No studies could be found in literature comparing ultrasound diagnosis with Tzanaki score in appendicitis. Results: The sensitivity, specificity, positive predictive value and negative predictive value of ultrasound were 73%, 50%, 95% and 12% respectively. The sensitivity, specificity, positive predictive value and negative predictive value of Tzanaki were 87%, 50%, 96% and 23% respectively. Tzanaki score is better than ultrasound alone as a diagnostic test for acute appendicitis. Conclusion: Tzanaki score is better than ultrasound in diagnosis of acute appendicitis.